Impactos sociales de la actividad petrolera en Ecuador: un análisis de los indicadores - Bustamante, Teodoro (2005)
This paper analyzes in what measure, the oil production process in Eastern Ecuador shows a specific profile in a hundred social indicators. The data used come from INFOPLAN, SIISE, census series, and oil production information. The correlations between different figures analyzed are studied, factor analysis and clusters are used to establish different groupings. The results show that oil activity produces a specific profile, but is not the main factor that explains or is associated to the differences in social indicators in the Ecuadorian Amazon basin.